Unpredictable Americas: Resignifying Americanness Under a Relational Perspective - Bernd, Zilá (Review of International American Studies, 2016)
Zilá Bernd Universidade Federal do Rio Grande do Sul Centro Universitário La Salle Brazil Unpredictable Americas: Resignifying Americanness Under a Relational Perspective Abstract: This presentation is a reflection originating in the representation of the Americas in its first iconographies (Marten de Vos, Jan van der Straet), from which a cultural hierarchical principle installed itself in detriment of the American culture. For five hundred years since the “discovery” of America we have been invested in deconstructing this feeling of supposed cultural dependence. The most successful strategy has been the search for a long memory, not in Europe, but in the native cultures, and that points to transcultural practices, initiated in the first centuries after the conquest when the Guarani reproduced models from the European baroque in sculptures with altered skin color, eye shape and ornaments. Oswald de Andrade and Edouard Glissant introduce us into the search for our own ancestry in indigenous and creole cultures. The notion of Americaness, far from proposing the existence of a large homogenous narrative, tries to analyze dislocations, re-semantization of myths throughout the three Americas and the task of reappropriation characteristic of American cultures beyond narrow notions of nationality. To think Americanness as a heterogeneous construct implies leaving aside binaries such as civilization/barbarism or center/periphery in favor of including the diverse and the excluded third. In keeping with recent work such as that of Patrick Imbert, we count on the implosion of polarized thinking, on transnational exchanges and the natural disposition to the relational and transcultural encounters which will favor processes of reconstellation of the Americas. Keywords: Americanness. Long Memory. Transcultural Practices. Re-semantization. Reconstellation.